Desafios para a transferência de tecnologia entre universidade empresa: estudo de caso UTFPR campus Toledo - Marchetti, Ivanir (2024)
Technology transfer (TT) is a crucial process for transforming scientific discoveries into marketable solutions and products that benefit society. Universities serve as centers for generating knowledge that can be converted into products and services with positive impacts on the community. By collaborating with the private sector, universities redefine their role in society and are recognized as promoters of economic, social, and human resource development for the regions in which they operate. However, despite these benefits, there are still challenges to be overcome to ensure the success of TT. To identify these challenges at the Toledo Campus of the Federal Technological University of Paraná (UTFPR-TD), the patented intellectual assets at this Higher Education and Research Institution (IEP) under investigation were identified, classified, and analyzed through a documentary survey to understand their characteristics and strategic importance for the organization. At the same time, specific forms were developed to identify the profile of the institution's researchers and members of the business community. The literature review, information collected through the forms, and the documentary analysis of the intellectual assets served to support the preparation of the conclusive technical report. The results of this project allowed for the identification of the main challenges to TT at the institution in question, as well as the proposal of strategic actions to overcome them. It is concluded that it is essential to strengthen the integration between the university and companies, enhance innovation infrastructure, and encourage policies that facilitate the transfer process, promoting the maximization of the positive impact of research on society and the market.